Cognitive disorders and fitness of the elderly in residential homes in Bydgoszcz - Marta Podhorecka; Anna Turska; Dominika Gębka; Radosław Perkowski; Joanna Perkowska; Alina Jaroch; Klara Nicpoń-Nożewska; Michalina Radzińska; Anna Grzanka-Tykwińska; Walery Zukow; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2017)
Introduction. Process of ageing and the growing number of people in  retirement age is one of the main problems of the modern world.  Together with advancing age both fitness and mental capacity deteriorate. Research proves that there is dependence between cognitive functions and fitness of the elderly. Aim. The aim of the study was to compare fitness with cognitive functions among residents of residential home in Bydgoszcz.  Material and methods. 59 people (35 women and 24 men) at the age of 60 to 98 participated in the study. Mini-Mental State Examination (MMSE) was used to assess cognitive functions.  Fitness was assessed by means of Tinetti Test. The subjects were divided according to a) age: group 60-75 and 75+ and b) gender. Results. Negative correlation was observed between age and Tinetti Test results. In the study there was positive and moderate correlation between MMSE scale and Tinetti Test results. In Tinetti Test results regarding differences due to gender were close to statistical significance.  Conclusions. There is a dependence between age and weakening of fitness in the elderly in residential homes in Bydgoszcz. Risk of falls increases with age. There is a dependence between cognitive functions disorders and fitness of the elderly from residential homes in Bydgoszcz.